Aplikasi Motion Detection untuk Home Security System dengan Pelaporan Otomatis Berbasis SMS Gateway - I Gede Made Adi Arta Wibawa; I Gede Mahendra Darmawiguna; I Made Gede Sunarya (KARMAPATI (Kumpulan Artikel Mahasiswa Pendidikan Teknik Informatika), 2013)
Changes due to the influence of human activity more modern era, requiring to leave the house more often. Such a situation is often the target of crime. This study aims to develop a software that can be used as a home security system that is used to monitoring the situation around by a camera equipped with the ability to detect the presence of motion by applying spatial domain method. The methods of spatial domain itself is a method used to examine and analyze the differences between the point processing images with image references comparator continuously captured by the camera. In the spatial domain methods, there are three main processes, namely the determination of a reference image, making the image periodically, and make comparisons between image references with comparable image by comparing each pixel that is in the same location. The applications of Surveillance Camera System is developed by using the Java programming language editor of NetBeans IDE 7.3, and JMF 2.1.1e and SMSLib-v3.5.3 library. Whenever the application detects a movement, then the application will automatically perform the recording directly into the form of a video and then uploaded to the internet so that users can directly access wherever they are, Surveillance Camera System software will be more efficient in terms of storage requirements for each time motion recording process. Furthermore, the application will notify the user via message feature. Motion detection by application Surveillance Camera System can detect human movement is 100% stable on lighting conditions is the level of detection sensitivity is set at 20.